Therapeutic Mechanism of Zhuyang Tongbian Decoction in Treating Functional Constipation: Insights from a Pilot Study Utilizing 16S rRNA Sequencing, Metagenomics, and Metabolomics - Zhang X; Yin H; Yang X; Kang J; Sui N (International Journal of General Medicine)
Xuan Zhang,1,* Hang Yin,2,* Xu Yang,3,* Jie Kang,1 Nan Sui1,4 1Graduate School, Liaoning University of Traditional Chinese Medicine, Shenyang, Liaoning Province, People’s Republic of China; 2Scientific Education Section, The Third Affiliated Hospital of Liaoning University of Traditional Chinese Medicine, Shenyang, Liaoning Province, People’s Republic of China; 3Department of Rehabilitation Medicine, General Hospital of Northern Theater Command, Shenyang, Liaoning Province, People’s Republic of China; 4Department of Anorectal Diseases, The Third Affiliated Hospital of Liaoning University of Traditional Chinese Medicine, Shenyang, Liaoning Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Nan Sui, The Third Affiliated Hospital of Liaoning University of Traditional Chinese Medicine, No. 35, Eleventh Wei Road, Shenyang, Liaoning, 110003, People’s Republic of China, Email suinan2226@163.comPurpose: To explore the mechanism of Zhuyang Tongbian Decoction (ZTD) in treating functional constipation (FC) by observing its effects on intestinal flora composition, the metabolic function of gut microbiota, fecal short-chain fatty acid (SCFA) levels, and serum concentrations of TLR4, NF-κB, TNF-α, and IL-6 in patients with FC.Patients and Methods: 40 patients with FC were randomly divided into the control group and the treatment group, 20 cases in each group. And 20 healthy volunteers were recruited during the same period. The control group was administered lactulose, while the treatment group was treated with ZTD. 16s RNA sequencing technology was used to compare the changes in the structure and diversity of the intestinal flora of patients before and after treatment. Changes in the levels of SCFAs in faeces and the levels of TLR4, NF-κB, TNF-α and IL-6 in serum were analysed. Metagenomics sequencing assessed microbiota metabolic functions.Results: The treatment group showed a significant increase in the relative abundance of beneficial bacteria, including Bifidobacterium, Lactobacillus, and Faecalibacterium_prausnitzii (P < 0.05), whereas Desulfobacterota and Ruminococcus were significantly reduced (P < 0.05). Notably, fecal acetic and propionic acid levels were significantly higher in the treatment group (P < 0.05). Serum biomarkers TLR4, NF-κB, TNF-α, and IL-6 decreased significantly (P < 0.05). Metagenomics sequencing showed that Carbohydrate metabolism, Metabolism of cofactors and vitamins, and C5- Branched dibasic acid metabolism were significantly increased in functional abundance (P < 0.05).Conclusion: ZTD notably improves intestinal flora composition and gut microbiota metabolic function, regulates SCFA levels, and reduces inflammation markers in FC patients. The strain Faecalibacterium_prausnitzii shows significant potential in regulation of intestinal inflammation and may play a crucial role in the treatment efficacy of ZTD for FC.Keywords: Zhuyang Tongbian Decoction, functional constipation, intestinal flora, metabolite, intestinal inflammation